2005
DOI: 10.1002/ps.1113
|View full text |Cite
|
Sign up to set email alerts
|

Rice (Oryza sativa) response to drift rates of glyphosate

Abstract: Greenhouse and field studies were conducted to investigate response of two rice varieties, Priscilla and Cocodrie, to sub-lethal rates of glyphosate in terms of injury, shikimate accumulation and yield. In the greenhouse, more shikimate accumulated in Cocodrie than Priscilla at comparable glyphosate rates applied to plants at the three-leaf stage. In field studies, glyphosate was applied to both varieties when they were 74-cm tall and in the internode separation growth stage. Visual injury, plant height, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 12 publications
2
86
0
5
Order By: Relevance
“…Reddy et al [4] found that glyphosate application on non-GR soybean could induce reduction of leaf chlorophyll content and decrease nodule biomass and leghemoglobin content. Koger et al [5] found that visual injury and plant height reduction could be observed for rice within seven days after glyphosate treatment. More recently, Reddy et al [6] reported that, in an aerial glyphosate drift experiment, chlorophyll reduction is about 80% for non-GR soybean leaves sprayed with 0.866 kg· ae/ha glyphosate solution, and higher than 40% for non-GR cotton leaves within one week after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Reddy et al [4] found that glyphosate application on non-GR soybean could induce reduction of leaf chlorophyll content and decrease nodule biomass and leghemoglobin content. Koger et al [5] found that visual injury and plant height reduction could be observed for rice within seven days after glyphosate treatment. More recently, Reddy et al [6] reported that, in an aerial glyphosate drift experiment, chlorophyll reduction is about 80% for non-GR soybean leaves sprayed with 0.866 kg· ae/ha glyphosate solution, and higher than 40% for non-GR cotton leaves within one week after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Matallo et al (2009), trabalhando com glyphosate e concentração de ácido chiquímico em citros, observaram que as plantas que receberam aplicação de glyphosate mostraram sempre maiores concentrações de ácido chiquímico que as plantas testemunhas. Vá-rios pesquisadores (Singh & Shaner, 1998;Wang, 2001;Mueller et al, 2003) (Mueller et al, 2003;Koger et al, 2005), algodão (Pline et al, 2002), girassol, trigo e milheto (Henry et al, 2007), soja (Singh & Shaner 1998) e trigo (Bresnahan et al, 2003.…”
Section: Resultsunclassified
“…Bresnahan et al (2003), verificando a concentração de ácido chiquímico com aplicação de glyphosate na cultura do trigo, observaram que o pico de concentração foi entre 7 e 10 dias após a aplicação e que os teores foram diminuindo até a colheita. Corroborando essa informação, Koger et al (2005) observaram que os picos de acumulação de ácido chiquí-mico ocorrem até 14 dias após o tratamento e que altos níveis foram detectados até 28 dias depois da aplicação do glyphosate.…”
Section: Resultsunclassified
“…Koger et al, 2005a), to distinguish resistant from susceptible soybean and cotton cultivars (Pline et al, 2002;Bonini et al, 2009), and to check its effect on the metabolism of aromatic amino acids in Cyperus rotundus (Wang, 2001). Transitory in nature, shikimic acid accumulation has been reported to occur one day after glyphosate application, reaching peak levels between four and seven days afterwards (Koger et al, 2005b).…”
Section: Measurementmentioning
confidence: 99%